Supplementing a Clay Mineral-Based Feed Additive Modulated Fecal Microbiota Composition, Liver Health, and Lipid Serum Metabolome in Dairy Cows Fed Starch-Rich Diets - Pacífico, Cátia; Hartinger, Thomas; Stauder, Alexander; Schwartz-Zimmermann, Heidi Elisabeth; Reisinger, Nicole; Faas, Johannes; Zebeli, Qendrim (Frontiers in Veterinary Science, 2021)
Starch-rich diets are needed to support milk performance in dairy cows but they increase the risk of gut dysbiosis and related systemic health disorders. This study aimed to evaluate the effects of supplementing a clay mineral-based feed additive (CM) on fecal microbiota structure and composition, fermentation, serum metabolome, and liver health variables in primiparous (PP) and multiparous (MP) early lactation cows. The experiment involved 24 cows randomly assigned to either a control or CM group, and fed a diet moderate and high in starch. Our data showed that supplementing the CM-based product reversed the decrease of the indices of bacterial diversity, richness and evenness during high-starch diet, demonstrating that the supplementation efficiently eased hindgut dysbiosis. The treatment significantly reduced levels of lactate-producing genus Lactobacillus in PP cows during starch-rich feeding and elevated fecal pH, indicating a healthier hindgut milieu compared to control. At the systemic level, supplementing the CM-based product during high-starch feeding increased the concentrations of the main primary bile salts and secondary bile acids in the serum, and improved liver function in cows as indicated by reduced levels of glutamate dehydrogenase and γ-glutamyl-transferase, as well as higher serum albumin and triglyceride concentrations. These changes and those related to lipid serum metabolome were more pronounced in PP cows as also corroborated by relevance network analysis.